2017
DOI: 10.1016/j.eats.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Anterolateral Arthroscopic Posterior Subtalar Arthrodesis: The Surgical Technique

Abstract: The effectiveness of subtalar arthrodesis has been well documented in treating degenerative subtalar joint disease. The arthroscopic subtalar approach for arthrodesis has also been proved to give excellent results in terms of bone fusion rates and reduction of wound-related pain and complications. To date, the main concerns about arthroscopy have regarded incision-related neurologic complications such as lesions of the tibial, fibular, and sural nerves. In this context, we present a 2-portal lateral (anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
5
0
4
Order By: Relevance
“…The issue whether a bone graft, an autologous bone graft, an allogenous bone graft, or an artificial bone graft is needed in arthroscopy-assisted subtalar arthrodesis remains controversial [9,10]. However, the most important finding of the present research was that each type of bone graft may have no significant difference for arthroscopy-assisted subtalar arthrodesis [11,12].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The issue whether a bone graft, an autologous bone graft, an allogenous bone graft, or an artificial bone graft is needed in arthroscopy-assisted subtalar arthrodesis remains controversial [9,10]. However, the most important finding of the present research was that each type of bone graft may have no significant difference for arthroscopy-assisted subtalar arthrodesis [11,12].…”
Section: Discussionmentioning
confidence: 70%
“…d The lateral X-ray of right ankle after surgery showed subtalar joint fixed in functional position. e The frontal X-ray of right ankle at the last followup 24 months showed full osseous fusion of the subtalar joint; F. The lateral X-ray of right ankle at the last follow-up 24 months showed full osseous fusion of the subtalar joint defect [10]. Due to no obvious deformity of the ankle and no bone defect in this research, we have finished arthroscopyassisted arthrodesis without bone graft implantation in the no bone graft group.…”
Section: Discussionmentioning
confidence: 80%
“…5,21,27,28 The posterior subtalar surface can be prepared under lateral arthroscopic guidance and subtalar arthrodesis can be done. 8,24,29 Studies of arthroscopic subtalar arthrodesis showed good results with low rates of complications, 30 a bone rate fusion greater than 90% with a shorter time to fusion (average of 8 weeks), and a quicker recovery. 16,17,[30][31][32][33] In conclusion, the arthroscopic resection of TCC and subtalar arthrodesis during the same procedure by using 2 lateral portals can be done for correctly selected patients.…”
Section: Discussionmentioning
confidence: 99%
“…The first portal achieved is the sinus tarsi portal using the technique described by Lintz and colleagues 7 in the context of performing subtalar arthrodesis via the anterolateral portal. The sinus tarsi is identified by digital palpation, and an incision of ∼4 mm is made.…”
Section: Surgical Techniquementioning
confidence: 99%